Performance and Implementation Evaluation of TR PAPR Reduction Methods for DVB-T2 - Mohamad Mroué; Amor Nafkha; Jacques Palicot; Benjamin Gavalda; Nelly Dagorne (International Journal of Digital Multimedia Broadcasting)
High Peak to Average Power Ratio (PAPR) is a critical issue in multicarrier communication systems using Orthogonal Frequency Division Multiplexing (OFDM), as in the Second Generation Terrestrial Digital Video Broadcasting (DVB-T2) system. This problem can result in large performance degradation due to the nonlinearity of the High Power Amplifier (HPA) or in its low power efficiency. In this paper, we evaluate the performance of different Tone Reservation-based techniques for PAPR reduction in DVB-T2 context. Also, we propose an iterative TR-based technique called “One Kernel One Peak” (OKOP). Simulation results and performance comparison of these techniques in terms of gain in PAPR reduction, mean power variation, and complexity will be given. Finally, we describe the implementation of a PAPR reduction algorithm in the DVB-T2 modulator.